A Framework for Understanding the Role of Spirituality in Health - Kirti Ranchod (South African Journal of Arts Therapies)
In the context of the current mental health crisis, integrating spirituality into healthcare presents both opportunities and challenges for improving health and advancing health equity. While mainstream biomedical systems often exclude Indigenous knowledge and spiritual practices, these cultural traditions provide significant, often underappreciated, benefits for health. The role of visual art, as part of spiritual practices, offers a compelling example of how sacred forms can be utilized in health interventions. Research shows that creating and viewing visual art activates brain networks associated with emotional regulation and self-awareness, suggesting potential benefits for people coping with various health conditions. However, challenges arise when attempting to integrate spirituality into biomedical healthcare systems. The tension between subjective, spiritual experiences and the objective, evidence-based demands of public health requires careful, respectful approaches to avoid harm and ensure beneficial outcomes. Dialogical approaches that respect plural definitions of health and foster inclusive, collaborative discussions are essential for creating a holistic, accessible healthcare system that embraces diverse spiritual practices.